Promoting a purpose-fostering approach in educators’ training through a group-based digital narrative design - Laura Fedeli (Ricerche di Pedagogia e Didattica, 2019)
Purpose development is a construct that can acquire a major focus in early adulthood when addressing university students’ educational process. The article presents an exploratory study run within the course “Educational Technologies” of the three-year degree for social educators’ training. The study aims at investigating (1) the impact of service-learning approach on the development of purpose and (2) the transformative role of a prosocial task developed through a digital storytelling design. Students were, in fact, actively engaged in the design and creation of a short video artefact linked with a specific social context in which they have chosen to apply for their forthcoming internship. The video artefact should represent the outcome of a synergic effort of both class peers and the territory actors since students were encouraged to actively interact with community beneficiaries and their educators.